Economic Potential Analysis of Malinau Regency - Agus Tri Darmawanto; Erick Karunia; Jumadi Jumadi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study examines the economic structure and development potential of Malinau Regency using Location Quotient (LQ), Klassen Typology, and Shift Share analyses. The findings indicate that mining and quarrying, water supply and waste management, construction, accommodation and food services, and public administration function as base and rapidly growing sectors with substantial comparative and competitive advantages. Manufacturing, trade, transportation, financial services, education, and health are identified as potential sectors with high growth but limited contributions. Conversely, agriculture, electricity and gas, and information and communication remain relatively underdeveloped. Overall, the regional economy remains highly dependent on the mining sector, underscoring the importance of economic diversification to achieve balanced, sustainable development.